Pigmented purpuric dermatoses: A review - Neema Shekhar; Ranjan Eeshaan; Durga Madhab Tripathy; Mani Siddharth; Oberoi Bhavni (Pigment International)
Pigmented purpuric dermatosis (PPD) comprises a group of skin conditions characterized by flat, nonpalpable petechiae and purpura as a result of capillaritis. Although the precise cause of PPD is as yet unknown, increased vascular permeability and capillary fragility are key factors in its pathophysiology. PPD has diverse clinical presentations, but the histopathology of all these variants essentially remains the same. The initial purpuric lesions develop a golden-brown hue owing to hemosiderin absorption and eventually progress to chronic pigmentary changes. These lesions, which often affect the lower limbs, are either asymptomatic or accompanied by moderate pruritus, and can be difficult to diagnose and treat. There are several subtypes of clinical presentations that have been documented over the years. In order to accurately diagnose PPD, a thorough clinical evaluation and, occasionally, a biopsy may be required. It is essential to identify the condition and reassure patients of its benign nature. Treatment is usually necessary due to the chronic nature of the condition, its consequences on physical and mental well-being, and the presence of significant lesions or itching. In this review, we outline the various prevalent PPDs and discuss their etiopathogenesis, clinical features, and diagnostic and treatment modalities.